2005
DOI: 10.1111/j.1467-9280.2005.01639.x
|View full text |Cite
|
Sign up to set email alerts
|

Pronouns in Marital Interaction

Abstract: Recent studies in social psychology have found that the frequency of certain words in people's speech and writing is related to psychological aspects of their personal health. We investigated whether counts of "self" and "other" pronouns used by 59 couples engaged in a problem-solving discussion were related to indices of marital health. One spouse in each couple had a diagnosis of obsessive-compulsive disorder or panic disorder with agoraphobia; 50% of the patients and 40% of their spouses reported marital di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
196
4
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(223 citation statements)
references
References 20 publications
(19 reference statements)
19
196
4
4
Order By: Relevance
“…These effects remained even after controlling for level of commitment to the offender, severity of the offence, and how long ago the offence took place. Although such differences in language use are very subtle, they appear to be related to several indicators of relationship functioning (Acitelli, 1998;Aron, Aron, & Smollan, 1992;Simmons, Gordon, & Chambless, 2005).…”
Section: Forgiveness In Personal Relationships 229mentioning
confidence: 99%
“…These effects remained even after controlling for level of commitment to the offender, severity of the offence, and how long ago the offence took place. Although such differences in language use are very subtle, they appear to be related to several indicators of relationship functioning (Acitelli, 1998;Aron, Aron, & Smollan, 1992;Simmons, Gordon, & Chambless, 2005).…”
Section: Forgiveness In Personal Relationships 229mentioning
confidence: 99%
“…In contrast, Pennebaker & King (1999) found that women consistently used "I", "me", and "my" at higher rates in personal essays. Finally, Simmons et al (2005) found a positive relationship between first person singular use in marital interactions and relationship satisfaction. In contrast, Sillars, Shellen, McIntosh and Pomegranate (1997) reported a negative correlation based on a slightly different design.…”
mentioning
confidence: 99%
“…Pennebaker and Lay (2002) have discussed that "we" can variously be a marker of communal perspective and occasionally used as a "royal we" signaling power differences ("We have to clean this mess up"). Although the empirical evidence that "we"-talk has been replicated several times in different labs (Seider et al, 2009;Sillars et al, 1997;Simmons et al, 2005), the limitations of the LIWC-based counting approach is that the linguistic context cannot be taken into account and needs to be investigated with other language analysis methods. Accordingly, on one hand higher use of "we"-talk by male participants might mirror the de-escalation behavior of male partners in previous findings by applying a communal perspective over the discussion (Carstensen, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, "we"-words such as "we", "our", or "ours" are found to reflect togetherness, "we"-ness, and a communal orientation (Pennebaker & Lay, 2002). "We"-talk in couples was related to higher commitment (Agnew, Van Lange, Rusbult, & Langston, 1998), positive changes of symptoms in patients with heart failure (Rohrbaugh, Mehl, Shoham, Reilly, & Ewy, 2008), better health related behavior in patients with problematic alcohol use (Rentscher et al, 2015) and in smokers with lung problems (Rohrbaugh, Shoham, Skoyen, Jensen, & Mehl, 2012), better dyadic adjustment in couples (Robbins, Mehl, Smith, & Weihs 2013), and more positive solutions when discussing the top issue facing their relationship (Simmons et al, 2005). "We"-talk has been studied in conflict situations and found to be related to less negative emotion in middle-aged and old couples (Seider, Hirschberger, Nelson, & Levenson, 2009) and it was related to high relationship satisfaction in couples (Sillars et al, 1997).…”
mentioning
confidence: 99%
See 1 more Smart Citation